The Students’ Perception through the Implementation of Contextual Teaching Method in Learning Speaking in Senior High School - Lisanty, Fibri Indira; Rahayu, Sri (FOSTER: Journal of English Language Teaching, 2023)
The objective of the research is to find out the students’ perception through the implementation of contextual teaching method in learning speaking at the second grade students of SMA Negeri 1 Malili . This research applied descriptive quantitative method. The population of this research was the second grade students of Exact Study Program in SMA Negeri 1 Malili. The researcher used total random sampling which the researcher took 25 students from one class. In collecting the data, the researcher used questionnaire to find out the students perception through the implementation of contextual teaching method in learning speaking. The result of the research shows that the students gave very good classification through the implementation of contextual teaching method. Based on the data from the questionnaire, the researcher concluded that the students’ perception through the implementation of contextual teaching method in learning speaking at the second grade students of SMA Negeri 1 Malili is very good based on the total score of the students’ peception was 1410 (Score range 1400 – 1750) and the mean score of the anwer of questionnnaire is 280.